2019
DOI: 10.31234/osf.io/z2q5j
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cognitive Basis for The Split-attention Effect

Abstract: The split-attention effect entails that learning from spatially separated, but mutually referring information sources (e.g., text and picture) is less effective than learning from the equivalent spatially integrated sources. According to cognitive load theory, impaired learning is caused by the working memory load imposed by the need to distribute attention between the information sources and mentally integrate them. In this study, we directly tested whether the split-attention effect is caused by spatial sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Other visual features, like text segmentation and picture labelling, were basically the same as the original materials. Several studies have shown that spatial separation/integration on its own may not be sufficient to impact learning outcomes (e.g., Florax & Ploetzner, 2010; Pouw et al, 2019). Therefore, we suspect that the higher visual complexity could be the reason for not finding the split‐attention effect in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Other visual features, like text segmentation and picture labelling, were basically the same as the original materials. Several studies have shown that spatial separation/integration on its own may not be sufficient to impact learning outcomes (e.g., Florax & Ploetzner, 2010; Pouw et al, 2019). Therefore, we suspect that the higher visual complexity could be the reason for not finding the split‐attention effect in our study.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the decomposition into smaller modules decreases the inherent process model complexity that may result in a higher ease of use, since the comprehension of smaller modules is associated with less cognitive load. However, note that this aspect, in turn, may cause opposing effects in the modularization of process models (e.g., split-attention effect [63]). In general, such impairing effects should be considered in modularized process models (see Section IV-G) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Ninth, although a reduction in the cognitive load during process model comprehension can be achieved with the application of modularization (e.g., reduction of process model complexity), however, other cognitive effects may emerge, which in turn have a negative effect on the comprehension of such models. For example, the depiction of a process model into smaller process models leads to the circumstance that the attention of an individual must be split between the smaller modules in order to ensure a proper model comprehension (i.e., split-attention effect [63]). As a result, the split attention may cause a higher cognitive load [43].…”
Section: E Limiting Factorsmentioning
confidence: 99%
“…Split-attention effect. The split-attention effect (Pouw, Rop, De Koning, & Paas, 2019;Tarmizi & Sweller, 1988) holds that students learn more from one integrated source of information than from multiple sources of information distributed either in space (spatial split attention) or time (temporal split attention). Learning from distributed sources of information requires more attentional switching and therefore makes the mental integration process that is needed to understand the learning task more difficult than learning from integrated sources.…”
Section: The Learning Tasksmentioning
confidence: 99%